Cirebon Mask Dance as an Ethnoscience Context in Project-Based Learning: Enhancing Students’ Creative Thinking and Science Process Skills - Bastian, Norma; Wibowo, Toni Ari (Ann Publisher, 2026)
Aims. This study investigates the effectiveness of Ethno-Project-Based Learning (E-PjBL) integrated with Cirebon Mask Dance (Tari Topeng Cirebon) as an ethnoscience context in enhancing students’ creative thinking skills and science process skills. Methods. Employing a quasi-experimental design with a pretest-posttest control group model, this research involved 72 junior secondary school students (Grade VIII) in Cirebon, West Java, Indonesia, divided into an experimental group (n = 36) receiving E-PjBL instruction and a control group (n = 36) receiving conventional inquiry-based learning. Data were collected using the validated Creative Thinking Skills Test (CTST), which assesses Torrance’s four dimensions (fluency, flexibility, originality, and elaboration), and the Science Process Skills Assessment (SPSA), which encompasses observing, classifying, predicting, hypothesizing, experimenting, and communicating. Statistical analyses using ANCOVA, N-gain scores, and effect size (Cohen’s d) revealed that the experimental group demonstrated significantly higher gains in creative thinking skills (ΔM = 18.73; p < .001; d = 1.42) and science process skills (ΔM = 21.46; p < .001; d = 1.67) compared to the control group. Result. Thematic qualitative analysis of student project artifacts and reflective journals further confirmed that the cultural symbolism embedded in the Cirebon Mask Dance, particularly its philosophical motifs that represent natural phenomena, served as authentic, meaningful stimuli for scientific inquiry and creative ideation. Conclusion. These findings establish E-PjBL as a culturally responsive pedagogical framework that bridges indigenous ecological knowledge with formal science education, offering a replicable model for ethnoscience integration in multicultural science classrooms.